KECENDERUNGAN KONTEKS KAJIAN FILM ISLAMI DI INDONESIA : LITERATURE REVIEW - Hariani, Nurul; Abdul (Jurnal Dakwah Tabligh, 2023)
This study aims to describe the tendency of the context of Islamic film studies in Indonesia using the Literature Review method. The results of this study have an argument that the study of Islamic films in Indonesia has a tendency in the context of research, namely Representation, Reception, Content of Da’wah Messages, Interpretation, and Resistance. First, the context of representation is dominant and can be analyzed through almost all approaches to the study of film media texts. Second, the Reception context has the consistency of Stuart Hall’s Reception theory and the Hermeneutics paradigm. Third, the context of the content of the message of Da’wah is dominantly associated with content analysis and semiotics. Fourth, the interpretation context is identified as a research context aimed at constructing meaning based on an object or subject. Fifth, the context of Resistance becomes a recommendation if the research aims to examine the phenomenon of social conflict in the form of efforts to change stigma or stereotypes. Research on resistance in Islamic films becomes urgent when it is related to the current reality, where there are still many social issues that link to Islam. Keywords: Islamic Film Studies, Representation, Reception, Contents of Da’wah Messages, Interpretation, Resistance